The tourism image of Estonia in Spain: a formulative approach - Katlin Savva; Arta Antonovica; Javier de Esteban Curiel (Nóesis)
We are living in an environment, where information flow is freer than ever. Nowadays everyone has access to global news and can make their own conclu-sions based on the perceived image. Therefore, the role of perception and image is becoming more important for different countries to attract visitors and in-vestors. Tourism is a way of selling the image of a country and the reputation and word of mouth generated from tourism activities are priceless to the image of a destination. This paper analyzes the case of Estonia, which is an emerging tourism market and quite new and unknown for Spain. The authors try to accent the importance of direct promotion, through a survey carried out to 341 Spanish people in Madrid. The result from this quantitative and formulative research method is that Estonia has to promote its tourism image better if the country wants to attract the Spanish tourist.